Recent development of oxygen evolution electrocatalysts in acidic environment - An, Li (2021)
The proton exchange membrane (PEM) water electrolysis is one of the most promising hydrogen production techniques. The oxygen evolution reaction (OER) occurring at the anode dominates the overall efficiency. Developing active and robust electrocatalysts for OER in acid is a longstanding challenge for PEM water electrolyzers. Most catalysts show unsatisfied stability under strong acidic and oxidative conditions. Such a stability challenge also leads to difficulties for a better understanding of mechanisms. This review aims to provide the current progress on understandings of OER mechanisms in acid, analyze the promising strategies to enhance both activity and stability, and summarize the state-of-the-art catalysts for OER in acid. First, the prevailing OER mechanisms are reviewed to establish the physicochemical structure-activity relationships for guiding the design of highly efficient OER electrocatalysts in acid with stable performance. We then discuss the reported approaches to improving the activity, from macro-view to micro-view. To analyze the problem of instability, the key factors affecting catalyst stability are summarized and the surface reconstruction is discussed. Various noble-metal based OER catalysts and the current progress of non-noble-metal based catalysts are reviewed. Lastly, the challenges and perspectives for the development of active and robust OER catalysts in acid are discussed.